Estimating and Monitoring the Land Surface Temperature (LST) Using Landsat OLI 8 TIRS - Muhammad Rais Abidin; Rahmi Nur; Erikha Maurizka Mayzarah; Ramli Umar (International Journal of Environment, Engineering and Education, 2021)
Land Surface Temperature (LST) is average temperature of an element of the exact surface of the Earth calculated from measured radiance which depends on the albedo, the vegetation cover, and the soil moisture. Land Surface Temperature can affect human discomfort, health problem, higher energy bill and further reduce the habitability of urban and sub urban area as Makassar city has been recently undergoing massive urban development. This study tries to monitor and estimate Land Surface Temperature by using Landsat 8 TIRS and the data analyzed by vegetation index, and temperature index in order to derive Land Surface Temperature value. The result shows that the vegetation area declined around 3470 hectares in the last four years while the urban area increased approximately 1509 hectare. In addition, 2015, Makassar, South Sulawesi, Indonesia are experienced the highest temperature at 32 degree Celsius while 2019 shown that the maximum heat reached 29 degree celsius. However, the moderate and high temperature (26 – 29 degree Celsius) in 2019 expand and cover wider area than in 2015 as the area of vegetation declined and built-up area increased significantly